PENGEMBANGAN PERANGKAT PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Margareta Margareta (LPD IKIP PGRI Pontianak, 2023)
our research is motivated by Bechagas Baul Gaelitan Askeluma who pays attention to subtle mathematical reasoning abilities and madah shows a good and effective hauf by developing a Taiwanese learning package. Review (SLR) Based on the results of the analysis, it is possible to train groups in the development of SALA mathematics with very good learning rates and effective tasks and demonstrate the ability to practice SESA mathematics in the instructorÂ Keywords: Learning media, students mathematical reasoning